BUDAYA KREATIVITAS DAN CO-CREATION DALAM STRATEGI MEDIA SOSIAL UKM KREATIF - Abdul Chamid; Wahyu Purno Irawan (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze how internal creativity culture and co-creation with external communities interact in shaping effective social media strategies in creative small and medium enterprises (SMEs). Using a qualitative approach with a single case study design at WSB, a figurine-based creative industry SME in Surabaya, data were collected through in-depth interviews with internal and external parties, participant observation, and digital artifact analysis. The findings indicate that WSB internalizes creativity culture through team autonomy, risk tolerance, and collaborative rituals involving all organizational functions. Co-creation mechanisms are implemented systematically with transparent dialogue, early access for the community, and formal recognition of fan contributions that build a sense of ownership and loyalty. The synergy of these two dimensions creates a dynamic capability that orchestrates internal and external ideas into authentic content that is emotionally resonant and adaptive to platform dynamics. Theoretically, this study expands the Resource-Based View perspective by positioning creativity culture and co-creation capacity as dynamic capabilities that transform intangible resources into sustainable competitive advantages. Practically, these results provide recommendations for creative SMEs to develop an inclusive creative ecosystem that positions social media as a strategic asset rather than a mere promotional channel.